The relationship between vitamin D level and insulin resistance in overweight Iraqi women - Jumaa, Abdulhadi Mohamed; Alamory, Nagham F. Khalil; Hussein, Yaseen Khashman; Younis, Rajaa Salih (American Journal of Biomedicine and Pharmacy, 2025)
Background: "Vitamin D deficiency and insulin resistance are common conditions associated with obesity and metabolic disorders. This study aimed to investigate the relationship between vitamin D levels and insulin resistance in overweight Iraqi women, with a focus on anthropometric measures such as body mass index (BMI) and waist-to-hip ratio (WHR). Methods: A cross-sectional study was conducted on 80 overweight and obese women (BMI ≥ 25 kg/m²) aged 18–72 years. Serum 25-hydroxyvitamin D levels and insulin resistance, assessed using the HOMA-IR index, were measured. Participants were stratified into three vitamin D categories: deficient (<20 ng/mL), insufficient (20–30 ng/mL), and sufficient (>30 ng/mL). Anthropometric and biochemical data were analyzed using SPSS software, employing correlation, ANOVA, and regression analysis. Results: The majority of participants (68%) had vitamin D deficiency, with a mean vitamin D level of 20.5 ± 10.3 ng/mL. A significant negative correlation was found between vitamin D levels and HOMA-IR (r = -0.42, p < 0.01). Women in the deficient group had higher mean HOMA-IR (3.8 ± 0.7) and BMI (38.0 ± 5.4 kg/m²) compared to the sufficient group (HOMA-IR: 2.9 ± 0.5, BMI: 33.1 ± 4.8 kg/m²). Linear regression indicated that for every 1 ng/mL increase in vitamin D, HOMA-IR decreased by 0.052 units (p < 0.001). WHR was independently associated with higher HOMA-IR, emphasizing the role of central obesity in insulin resistance. Conclusions: Vitamin D deficiency is strongly associated with increased insulin resistance in overweight women, compounded by obesity and central adiposity. These findings underscore the importance of addressing vitamin D deficiency and obesity through routine screening, targeted supplementation, and lifestyle interventions to reduce the risk of metabolic" disorders.